An Evaluation of the Contributing Factors of Water Scheme Failures in Nigeria - Andres, Luis; Chellaraj, Gnanaraj; Das Gupta, Basab; Grabinsky, Jonathan; Joseph, George (World Bank, Washington, DC, 2018)
This paper utilizes information from the 2015 Nigeria National Water and Sanitation Survey to identify the extent and timing of the failure of water schemes in the country and the factors affecting it. Around 46 percent of all the water schemes in Nigeria are nonfunctional, and approximately 30 percent are likely to fail in the first year. The results indicate that during the first year of operation, factors that can be controlled in the design, implementation, and operational stages contribute to the failure of 61 percent of the water schemes. As water schemes age, their likelihood of failure is best predicted by factors that cannot be modified. The influence of operational factors, such as repairs and maintenance, decreases slightly over time.